Solar influences on the Earth’s atmosphere: solved and unsolved questions - Georgieva, Katya; Veretenenko, Svetlana (Frontiers in Astronomy and Space Sciences, 2023)
The influence of the Sun on the Earth’s atmosphere and climate has been a matter of hot debate for more than two centuries. In spite of the correlations found between the sunspot numbers and various atmospheric parameters, the mechanisms for such influences are not quite clear yet. Though great progress has been recently made, a major problem remains: the correlations are not stable, they may strengthen, weaken, disappear, and even change sign depending on the time period. None of the proposed so far mechanisms explains this temporal variability. The basis of all solar activity is the solar magnetic field which cyclically oscillates between its two components – poloidal and toroidal. We first briefly describe the operation of the solar dynamo transforming the poloidal field into toroidal and back, the evaluated relative variations of these two components, and their geoeffective manifestations. The reversals of the correlations between solar activity and atmospheric parameters have a periodicity of 60 years and are related to the evolution of the main forms of large-scale atmospheric circulation whose occurrence has a similar periodicity. The large-scale circulation forms are in turn influenced by the state of the polar vortex which can affect the troposphere-stratosphere interaction via the propagation of planetary waves. Increased UV irradiance was found to lead to a negative phase of the North Atlantic Oscillation, while increased energetic particles result in a positive phase. The solar poloidal and toroidal fields are the two faces of the solar large-scale magnetic field. They are closely connected, but because they are generated in different domains and because of the randomness involved in the generation of the poloidal field from the toroidal field, on longer time-scales their variations differ. As a result, in some periods poloidal field-related solar drivers prevail, in other periods toroidal field-related drivers prevail. These periods vary cyclically. When the poloidal field-related drivers prevail, the stratospheric polar vortex is stronger, and the correlation between solar activity and atmospheric parameters is positive. When toroidal field- related drivers prevail, the vortex is weaker and the correlations are negative.